Fourth Plan Report of the Working Group on Machine Tools (Group VI-July, 1964) - Planning Commission (Planning Commission, 1964)
Pursuant to the decision taken at the fifth meeting of the Planning Group for Machinery Industries held on 18th September, 1963, a number of Working Groups were constituted. One of these, Group VI was for the Machine Tool industry.
Planning Group on Machinery Industries